Aberrant Receptor-Mediated Endocytosis of Schistosoma mansoni Glycoproteins on Host Lipoproteins - Sprong, Hein (Public Library of Science, 2006)
BACKGROUND: Bilharzia is one of the major parasitic infections affecting the public health and socioeconomic circumstances in (sub) tropical areas. Its causative agents are schistosomes. Since these worms remain in their host for decades, they have developed mechanisms to evade or resist the immune system. Like several other parasites, their surface membranes are coated with a protective layer of glycoproteins that are anchored by a lipid modification. METHODS AND FINDINGS: We studied the release of glycosyl-phosphatidylinositol (GPI)-anchored proteins of S. mansoni and found them in the circulation associated with host lipoprotein particles. Host cells endocytosed schistosomal GPI-anchored proteins via their lipoprotein receptor pathway, resulting in disturbed lysosome morphology. In patients suffering from chronic schistosomiasis, antibodies attacked the parasite GPI-anchored glycoproteins that were associated with the patients' own lipoprotein particles. These immunocomplexes were endocytosed by cells carrying an immunoglobulin-Fc receptor, leading to clearance of lipoproteins by the immune system. As a consequence, neutral lipids accumulated in neutrophils of infected hamsters and in human neutrophils incubated with patient serum, and this accumulation was associated with apoptosis and reduced neutrophil viability. Also, Trypanosoma brucei, the parasite that causes sleeping sickness, released its major GPI-anchored glycoprotein VSG221 on lipoprotein particles, demonstrating that this process is generalizable to other pathogens/parasites. CONCLUSIONS: Transfer of parasite antigens to host cells via host lipoproteins disrupts lipid homeostasis in immune cells, promotes neutrophil apoptosis, may result in aberrant antigen presentation in host cells, and thus cause an inefficient immune response against the pathogen.